The Complication Of Decrease In Aorto-Mesenteric Angle And Distance Its Diagnosis And Treatment: Case Report - O. V. Galimov; V. O. Khanov; H.M. H. Karkhani; Sh. Bhawna; T. R. Ibragimov (Креативная хирургия и онкология, 2022)
Introduction. Wilkie syndrome is a pathological manifestation caused by an abnormal disorder of the superior mesenteric artery arising from the abdominal part of the aorta. As a result, the distal part of the duodenum is compressed between the abdominal aorta, spine, and SMA, which creates a hindrance for the passage of himus in the duodenum, creating a mechanical obstruction.Aim: To draw the surgeons’ attention towards the possibility of developing a rare complication of decreased aorto-mesenteric angle and the distance, highlighting the challenges in diagnosis and treatment.Materials and methods. This article presents a clinical case of WS diagnosed in the surgical department of the BSMU clinic. We hereby discuss the case report of a 28-year-old patient diagnosed at the initial stage of WS. The patient had been suffering from the symptoms of WS since 2018 but wasn’t able to identify the disease, but when he came to the surgical department of BSMU clinic based on the results of abdominal CT-scan with combined contrast of the stomach and duodenum per os with water-soluble contrast and computer angiography of the mesenteric vessels, the diagnosis was confirmed. The patient was treated with the duodenojejunostomy (laparoscopic Strong’s operation).Results and discussion. Absence of timely diagnosis of this disease can lead to life-threatening complications, and early diagnostics is complicated by similarity of initial manifestations with other gastropancreaticoduodenal diseases. One of the most promising approach in the diagnosis of Wilkie syndrome is the use of abdominal CT-scan with combined contrasting of the stomach and duodenum per os with water-soluble contrast and computer angiography of vessels. In the present clinical case due to the given combination of methods we can assess functional state of the stomach and duodenum, clearly visualize not only the organs topography but also estimate the aorto-mesenteric angle and distance, which can further determine the type and tactics of initial stage treatment, which we decided to perform surgery (laparoscopic Strong’s operation). The postoperative period was without complications. The patient noted an improvement in the state and the relief of pain in the epigastrium and was discharged after 9 days of hospitalization in satisfactory condition.Conclusion. For diagnosis and treatment in time as well as prevention of possible complications, it is necessary to improve surgeons’ information about this pathology, which if diagnosed and treated late can lead to severe, life-threatening complications up to death. The diagnosis at the initial stages, specifically with the assistance of computer tomography with contrast, angiography, and treatment in a timely manner, can preserve life and prevent the possible outcomes of fatal complications.